On the evolution of sub- and super-saturated water uptake of secondary organic aerosol in chamber experiments from mixed precursors - Y. Wang; Y. Wang; A. Voliotis; D. Hu; Y. Shao; M. Du; Y. Chen; Y. Chen; J. Kleinheins; C. Marcolli; M. R. Alfarra; M. R. Alfarra; et al. (Atmospheric Chemistry and Physics, 2022)
To better understand the chemical controls of sub- and super-saturated aerosol water uptake, we designed and conducted a series of chamber experiments to investigate the evolution of secondary organic aerosol (SOA) particle physicochemical properties during photo-oxidation of single and mixed biogenic (α-pinene, isoprene) and anthropogenic (o-cresol) volatile organic compounds (VOCs) in the presence of ammonium sulfate seeds. During the 6 h experiments, the cloud condensation nuclei (CCN) activity at super-saturation of water (0.1 %–0.5 %), hygroscopic growth factor at 90 % relative humidity (RH), and non-refractory PM1 chemical composition were recorded concurrently. Attempts to use the hygroscopicity parameter κ to reconcile water uptake ability below and above water saturation from various VOC precursor systems were made, aiming to predict the CCN activity from the sub-saturated hygroscopicity. The thermodynamic model AIOMFAC (aerosol inorganic-organic mixtures functional groups activity coefficients) was used to simulate κ values of model compound mixtures to compare with the observation and to isolate the controlling factors of water uptake at different RHs.